2009
DOI: 10.3109/09638230903111098
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supported employment on service costs and income of people with mental health needs

Abstract: Background: A 12-month study of UK supported employment providers found that 77 (54.6%) of the participants in the study remained unemployed, 32 (22.7%) got jobs and 32 (22.7%) retained the jobs they held at the outset. Aims: To explore the impact of moving into employment on service use, earnings, benefits and tax allowances claimed. Methods: Service use and frequency were measured at baseline and 12 months. Comparisons paid particular attention to the differences between people entering work and those who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Clients who do begin to work may experience an improvement in symptoms and self‐esteem , which might in turn reduce hospitalizations. Studies that have considered the effects of working on overall treatment costs do suggest that, in clients who enter into work (which IPS facilitates but does not guarantee), there are reductions in treatment costs , and these are largely influenced by inpatient use.…”
Section: Discussionmentioning
confidence: 99%
“…Clients who do begin to work may experience an improvement in symptoms and self‐esteem , which might in turn reduce hospitalizations. Studies that have considered the effects of working on overall treatment costs do suggest that, in clients who enter into work (which IPS facilitates but does not guarantee), there are reductions in treatment costs , and these are largely influenced by inpatient use.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several recent studies have reported on the relationship between employment and treatment costs (28)(29)(30). The observed negative correlations between employment and treatment costs might be seen as evidence of a treatment cost offset effect of IPS-SE services, because IPS-SE has a track record of increasing employment (1,29).…”
Section: Other Cost Offsets Of Ips-se For Mental Health Treatmentmentioning
confidence: 94%
“…In many studies, employment also correlates with short-term reductions in mental health costs (Bond et al, 1995;Burns et al, 2008;Clark, 1998;Henry, et al, 2004;Latimer, 2001;Perkins, Born, Raines, & Galka, 2005;Schneider et al, 2009). These savings can accumulate to large sums over time (Bush, Drake, Xie, McHugo, & Haslett, 2009).…”
Section: Non-vocational Outcomesmentioning
confidence: 99%
“…IPS generates two main cost offsets: reduced costs for mental health treatment and reduced participation in disability systems. Several studies demonstrate that supported employment services decrease mental health costs (Bond et al, 1995;Burns et al, 2008;Clark, Xie et al, 1998;Frey et al, 2011;Henry et al, 2004;Knapp et al, 2013;Latimer, 2001;Perkins et al, 2005;Schneider et al, 2009). While the preliminary evidence is encouraging for cost offsets exceeding the direct costs of IPS services, some economists remain cautious about overstating savings (Salkever, 2012).…”
Section: Cost Offsetsmentioning
confidence: 99%